The Impact of Indonesian Migrant Workers' Remittances on The Distribution of Household Income: Analysis of The Socio-Economic Balance System In 2008 - Permatasari, Siska Intan; Sugiharti, Lilik (Jurnal Ilmu Ekonomi Terapan, 2016)
This study aims to analyze the impact of Indonesian workers' remittances on income distribution of households, in which includes the total impact as well as the details of the road from the impact. The data used is the Social Accounting Matrix (SAM) of Indonesia in 2008. The methodology used is matrix multiplier balance with Leontief inverse analysis and details of the impact analyzed through decomposition of the matrix multiplier. The results of this study showed that the group of households that are affected most by the injection of remittances in the government sector is domestic agricultural entrepreneurs while the total impact on the production sector to get the most impact is the sector of Real Estate and Business Services sector, followed by trade.